Implementasi Model Team Games Tournament (Tgt) Dalam Upaya Meningkatkan Hasil Belajar Siswa Muatan IPAS Kelas IV SDIT Ulil Albab Kamal Bangkalan - Alifia Roudhotul Jannah; Agung Setyawan (BADAN PENERBIT STIEPARI PRESS, 2023)
Learning results are a thing obtained when an individual gets a learning and gives a change to an individual. The study aims to enhance the results of students' learning on load of ipas by applying a typical cooperative learning model. The research USES PTK design made by kmemis and MC taggart with through the four stages, namely, planing, acting, reflection, and reflection. Results in cycle 1 are found that the student of class iv scores over 70 out of 69%. Then on cycle 2 an increase of 94% students scored above 70.